Hydroetanolic extract activity of Raphanus Sativus leaves in submandibular glands of rats with diabetes mellitus (Research, Society and Development, 2021)
Diabetes mellitus (DM) is a disease identified by the high level of glucose in the blood that results from a defect in insulin secretion. Individuals with uncontrolled diabetes have important changes in the oral cavity, such as periodontitis and hyposalivation, making them more predisposed to cavities, dry mouth, in addition to affecting immunity and increasing susceptibility to infections. In this study, the activity of the hydroethanolic extract of Raphanus sativus (radish) was evaluated in decreasing oxidative stress in male wistar rats with diabetes induced by using Alloxane (120 mg / kg) and treated over a 90-day period with Raphanus Sativus extract daily by gavage at a concentration of 300 mg / kg / day. The tested extract showed positive results, since decreased oxidative stress was observed, as attested by evaluating lipoperoxidation (MDA) and protein oxidation in the submandibular glands of rats with diabetes. The hydroethanolic extract of Raphanus sativus has antioxidant effects, being able to reverse the damage caused by oxidative stress. The results of this work show that the extract of Raphanus sativus can become a therapeutic option for the control of oxidative damage from DM involving the oral cavity.